2019
DOI: 10.1103/physrevb.99.035306
|View full text |Cite
|
Sign up to set email alerts
|

Vacancies in SnSe single crystals in a near-equilibrium state

Abstract: The development of intrinsic vacancies in SnSe single crystals was investigated as a function of annealing temperature by means of positron annihilation spectroscopy accompanied by transport measurements. It has been demonstrated that two types of vacancies are present in single-crystalline SnSe. While Sn vacancies dominate in the low-temperature region, Se vacancies and vacancy clusters govern the high-temperature region. These findings are supported by theoretical calculations enabling direct detection and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…12 Therefore, Se and Te nanoclusters or fewlayer films can occur during crystal growth, especially near the sample edges, as proved in SnSe by positron annihilation spectroscopy. 79 It has also been proved that oxidation at ambient conditions seems to favor the presence of the ARMs. 18,21 On the other hand, it has also been shown that treatment with acid agents, like HCl, HF, and HNO3 lead to formation of Te layers in CdTe, while dilution of bromine in methanol removes the Te layer.…”
mentioning
confidence: 99%
“…12 Therefore, Se and Te nanoclusters or fewlayer films can occur during crystal growth, especially near the sample edges, as proved in SnSe by positron annihilation spectroscopy. 79 It has also been proved that oxidation at ambient conditions seems to favor the presence of the ARMs. 18,21 On the other hand, it has also been shown that treatment with acid agents, like HCl, HF, and HNO3 lead to formation of Te layers in CdTe, while dilution of bromine in methanol removes the Te layer.…”
mentioning
confidence: 99%
“…According to the results described earlier, a microcosmic mechanism of heat-induced surface structure transformation from SnSe into SnSe 2 could be inferred. As the Sn vacancy defect is the common defect in SnSe, [6,18,19] the migration of Sn ion will format the Schottky defect and nanosized Sn congeries upon the surface of SnSe. The sticky surface of the SnSe nanosheet is due to the semimolten Sn congeries.…”
Section: Resultsmentioning
confidence: 99%
“…Successful thermoelectric generators have been made based on SnSe very recently [64]. The effects of vacancy on the thermoelectric properties have been studied in detail [65][66][67][68]. Applied pressure transforms SnSe into a semimetal [69].…”
Section: Introductionmentioning
confidence: 99%